Breast Metastasis of Lung Cancer After Computed Tomography-Guided Core Needle Biopsy: A Case Report - Zhao, Rong; Xing, Jun; Gao, Jinnan (Frontiers in Surgery, 2022)
Background: Needle tract metastasis is a rare complication following percutaneous procedures for malignancy. Case summary: This report describes a 49-year-old female with a lump on her right breast. Mass core needle biopsy showed the specimen was an invasive carcinoma, and mastectomy with sentinel lymph node biopsy was performed. What is special about this case was that the patient reported a history of lung cancer and the position of the breast mass was the puncture site of computed tomography-guided core needle biopsy for lung cancer. Immunostaining of paraffin specimen findings indicated the breast mass as a result of lung carcinoma metastasis. The patient’s medical history indicated that the malignant tumor in the breast was a core needle tract pulmonary metastasis. The patient underwent the examination and received therapy based on the lung cancer metastasis principle. At 9 months from breast surgery, the patient is alive, in good condition, and with stability of the disease. Conclusions: This patient was misdiagnosed. Careful medical history review and multidisciplinary team discussions are important, especially for patients with a history of cancer or invasive operation.